The Canadian Pediatric Surgery Network (CAPSNet): Lessons Learned from a National Registry Devoted to the Study of Congenital Diaphragmatic Hernia and Gastroschisis - Butler, Alison E.; Puligandla, Pramod S.; Skarsgard, Erik D. (European Journal of Pediatric Surgery, 2015)
The Canadian Pediatric Surgery Network (CAPSNet) was created in 2005 by a geographically representative, multidisciplinary group of clinicians and researchers with the intent of establishing a national research registry for gastroschisis (GS) and congenital diaphragmatic hernia (CDH). Since then, CAPSNet has used this registry and its 16-center network to make contributions to the knowledge base informing best practices for GS and CDH care. More recently, CAPSNet has expanded its focus to include quality assurance and improvement at each of its sites, by issuing a benchmarked outcomes “report card” with its annual report. Finally, a major objective of CAPSNet has been to establish and adopt standardized, evidence-based practice guidelines for GS and CDH across all Canadian perinatal centers.
Keywords: congenital diaphragmatic hernia; gastroschisis; registry